La Unión Económica y Monetaria europea en el discurso periodístico británico - Sotelo González, Joaquín (Estudios sobre el Mensaje Periodístico, 2008)
This paper focuses on the topic of the introduction of the Euro in the main British national newspapers. The paper undertakes a content and frame analysis of journalistic treatment on the single currency from a key stage in the development of monetary union -the adoption of the Euro as legal tender across the member states belonging to EMU in January 2002. The study covers the most important periods surrounding the launch of the Euro and the analysis is based on articles taken from nine national newspapers representing the tabloid, mid-market and broadsheet sectors of the British newspaper market.